SYNTHESIS, CHARACTERIZATION AND PHOTOACTIVITY EVALUATION OF NITROGEN DOPED TITANIUM DIOXIDE ON METHYLENE BLUE DYE DEGRADATION - Yilleng, Moses Titus; Sunday, Moses; Stephen, Doctor (FUDMA Journal of Sciences, 2020)
Titanium dioxide has proven to be one of the most promising heterogeneous catalyst. This work explores the photocatalytic activity of modified titanium dioxide. Nitrogen was incorporated into mesoporous TiO2 using Sol-gel method. The N-TiO2 was characterized using X-ray diffraction (XRD), Fourier Transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), Scanning electron microscopy (SEM) thermogravimetric analysis (TGA), and U-Vis diffuse reflectance spectroscopy (DRS). 1%wtN-TiO2 expresses the highest photoactivity in UV light compared to 3%wtN-TiO2 and 5%wt N-TiO2 respectively. The photodegradation efficiency of the catalyst follows the following trend 1%wtN-TiO2 >3%wtN-TiO2 >5%wtN-TiO2>PURE-TiO2. The results obtained from the kinetics investigation shows the following trends 1%wtN-TiO2 is 0.049 s-1, 3%wtN-TiO2 is 0.0289 s-1, 5%wtN-TiO2 is 0.0143 s-1, and the PURE-TiO2 is 0.0118 s-1. The consistency in the rate constant values of the phodegradation of methylene blue; it clearly showed that the reaction follows a pseudo-first order kinetics.